THE EFFECT OF EMOTIONAL INTELLIGENCE AND CYNICISM ON EMPLOYEE PERFORMANCE IN THE HEALTH OFFICE SUNGAI PENUH CITY - Hendra Hendra (Citakonsultindo, 2025)
This study aims to determine the effect of emotional intelligence and cynicism on employee performance at the Health Office Sungai Penuh City in Sungai Penuh City both partially and simultaneously and the effect is large. The sample of this research is the Civil Servants at the Health Office Sungai Penuh City in Sungai Penuh City is 31 people. Testing of the research instrument was carried out on 31 Civil Servants at the Health Office Sungai Penuh City. Collecting data using the questionnaire method. The data analysis tools used are Descriptive Analysis, Multiple Linear Regression, and Coefficient of Determination and the hypothesis tests used are the t-test and F test. The results of this study show Emotional Intelligence has a significant effect on employee performance at the Kumun Debai sub-district office, this is evidenced by the t count > t table (2.505 > 2.11991) and the magnitude of the effect is 28.6%. Cynicism has no significant effect on employee performance at the Kumun Debai sub-district office, this is evidenced by t count < t table (-1.046 < 2.11991) and the magnitude of the effect is only 1.1%. Simultaneously there is a significant influence between Emotional Intelligence and Cynicism on Employee Performance at the Health Office Sungai Penuh City, This can be proven by F count > F table (F count > F table (7,777 > 3,24) and the magnitude of the effect is 59.3 %, while the remaining 40.7% is explained by other causal factors not examined in this study.